Cross her heart : a novel - Pinborough, Sarah, 1972- (William Morrow, an imprint of HarperCollinsPublishers, 2018)
"A hair-raising psychological thriller about a single mom and her friends, the secrets they hide, and the pasts they can't escape, from the New York Times bestselling author of Behind Her Eyes"--